Métodos híbridos para o problema de roteamento de veículos com janelas de tempo e múltiplos entregadores - Álvarez Díaz, Aldair Alberto (Universidade Federal de São Carlos, 2016)
In this dissertation we address the vehicle routing problem with time windows and multiple deliverymen, a variant of the vehicle routing problem that involves the additional decision of the crew size definition of the vehicles, besides scheduling and routing decisions. This problem arises in the distribution of goods in highly congested urban areas, where due to the relatively long service times, it may be difficult to serve all clients during regular working hours. Given this difficulty, an alternative consists in including the deliverymen assignment decision, which leads to extra costs in addition to travel and vehicle costs. The objective is to define routes to serve customer clusters minimizing the number of vehicles used, the number of allocated deliverymen and the traveled distance. In this study, we develop different solution methods to solve this problem. Initially, we present two metaheuristic approaches, which are based on Iterated Local Search and Large Neighborhood Search. Then we propose hybrid methods, combining these metaheuristics with a branch-price-and-cut method. Computational experiments using instances from the literature confirm the efficiency of the solution methods developed for the problem.
Keywords: Roteamento de veículos; Múltiplos entregadores; Métodos híbridos; Branch-price- and-cut; Metaheurísticas; Vehicle routing; Multiple deliverymen; Hybrid methods; Metaheuristics; ENGENHARIAS::ENGENHARIA DE PRODUCAO